Kajian Etimologi dan Terminologi Metodologi Pembelajaran Pendidikan Agama Islam - Darmiah Darmiah (Jurnal MUDARRISUNA: Media Kajian Pendidikan Agama Islam, 2022)
Islamic religious education as a system is an activity that includes objectives, curriculum, teachers, methods, approaches, infrastructure, environment, management and others that are interrelated and form a unified system. The student education methodology must be adapted to the needs and characteristics of students, so that teachers can easily convey it to students, and students can also easily accept and understand lessons from teachers, because teachers can adjust to students' souls. . students with such learning. Methodology comes from the Greek language and consists of two words, namely "Metodos" which means way or way and "Logos" which means science. In short, methodology is the science (discussion) of methods or methods. Although that method itself is the most convenient and fastest way to do things. There are also those who believe that the method is the path taken to achieve a goal. The definition of method in Zakia Drajat's terminology is a systematic way of working to facilitate the implementation of an action to achieve a goal. From Arifin's point of view, the method is the path one takes to achieve a goal. The definition of method in technical language is different. According to Hasan, Langgilang defines the method as a way or path that must be taken to achieve educational goals.